BRAND SWITCHING BEHAVIOUR PADA PRODUK SKINCARE HALAL DITINJAU BERDASARKAN PRIOR EXPERIENCE DAN VARIETY SEEKING BUYING BEHAVIOUR - Lestari, Nia Kurnia (UIN Sunan Gunung Djati Bandung, 2022)
Companies must be able to answer market challenges and take advantage of these challenges to become opportunities to survive in the future. If the company is unable to create advantages from the products it produces, the likelihood that consumers will make brand transfers to the products they consume will be higher. The objectives of this study are To understand the great influence of Prior Experience and Variety seeking Buying Behavior on Brand Switching Behavior in Wardah's skincare product consumers. The research method used in this study is an explanatory method with a quantitative approach. The data used are primary data obtained from questionnaires of respondents who are consumers of Wardah skincare products in Bandung. The results of simultaneously it was concluded that Prior Experience (X1) and Variety Seeking Buying behavior (X2) simultaneously had a positive and significant effect on Brand Switching Behavior (Y) in wardah skincare consumers in Bandung City, because the value of F count ≥ F table (11.302 ≥ 3.090). So, the prior experience factors using Wardah skincare products, as well as the factor to what extent the level of consumers' desire to seek variations on other products are two factors out of the many factors that can influence consumers to do so. brand shift.